Crafting a Sharia Fintech Development Strategy in Indonesia: Leveraging SWOT Analysis for Sustainable Growth - Faizin, Moh; Era Rosalina, Kenlies; Mahmudah, Siti Nur (El Barka: Journal of Islamic Economics and Business, 2024)
Abstract: The incorporation of sharia principles into financial technology offers a rare chance to harmonize contemporary financial services with Islamic ideals, particularly as Indonesia’s fintech industry continues to grow rapidly. This emerging industry, called Sharia fintech, is promoting ethical financial practices that appeal to a large segment of Indonesian society in addition to increasing access to financial services. The adoption of a strategic strategy that leverages strenghths, tackles weaknesses, seizes opportunities, and mitigates dangers is crucial for the sustained expansion of sharia fintech. An excellent tool for developing such a strategy is the SWOT analysis framework. With the largest muslim population in the world, Indonesia’s demographics are unquestionably favorable for sharia fintech. But what’s new is realizing that the ingrained cultural attachment to Islamic banking can be used as a driving force behind creative product development as well as a competitive advantage. Through the utilization of this cultural resonance, sharia fintech can actively influence financial behaviors that promote economic fairness, risk sharing, and ethical investment, rather than merely adhering to sharia law. Although there is clear demand for sharia compliant products, the finance industry still lacks comprehensive regulatory frameworks and regulated standards, which is a serious shortcoming. The novel aspect of this is that it promotes cooperation between academics, industry participants and regulators. This partnership has the potential to result in the creation of dynamic laws that are both in line with Islamic law and adaptable enough to take advantage of the fintech industry’s rapid innovation. Study This use method is qualitative with approach studies sourced literature from relevant articles, books, journals, and notes with a study to answer the problem formulated. Opportunities abound in Indonesia’s fintech scene, especially when it comes to increasing financial inclusion for marginalized groups. Leading this charge could be sharia fintech, which provides products that meet the unique financial requirements of these communities while still adhering to Islamic law. The innovation is in the way these products are conceptualized, connecting modern fintech to traditional Islamic financial procedurs. Examples include using blockchain to provide transparency in the distribution of zakat or developing AI powered risk assessment models that comply with sharia law. Based on the IFE and EFE analysis above can be concluded that that became obstacle in the most important development of sharia fintech in Indonesia is minimal knowledge of public villages For operating sharia fintech, the second is lack of source Power humans (HR) control contract transaction based sharia principles, then the third competition future technology, and finally that is development sharia fintech products with various type type contract.